2019
DOI: 10.1177/1937586719885376
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Visibility on Medical Teamwork in Emergency Departments: A Mixed-Methods Study

Abstract: Aim: This mixed-methods study delivers empirical evidence on the influence of visibility on healthcare teamwork in Emergency Departments (EDs). This study researchers hypothesized that with changes of visibility in EDs, teamwork among medical staff members will be impacted. Background: Prior research results suggest that visibility can influence health-setting efficacy. Teamwork is one of the components of each healthcare system that can be supported by environmental design. Method: Visibility in four subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Also, the findings were supported by other qualitative studies (Gharaveis, A., Hamilton, D. K., et al, 2019; Gharaveis et al, 2019). Recently, a group of authors (Gharaveis, A., Pati, D., et al, 2020) investigated the impact of visibility on teamwork in a mixed-methods study and found some visibility values are associated with efficient teamwork. What has not been fully addressed in these studies is the magnitude of influence visibility has on communication.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Also, the findings were supported by other qualitative studies (Gharaveis, A., Hamilton, D. K., et al, 2019; Gharaveis et al, 2019). Recently, a group of authors (Gharaveis, A., Pati, D., et al, 2020) investigated the impact of visibility on teamwork in a mixed-methods study and found some visibility values are associated with efficient teamwork. What has not been fully addressed in these studies is the magnitude of influence visibility has on communication.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Collaboration is a multifaceted and complex measure. Other factors like central location of the physicians’ workstation in the unit (Gharaveis et al, 2018), staff-staff visibility (Gharaveis et al, 2020), and proximity to the nursing stations (Weaver et al, 2017) may impact collaborative communication. One reason for insignificant results may be the use of a collaboration scale not meant to study the effect of design.…”
Section: Discussionmentioning
confidence: 99%
“…Zamani (2018) reported that the lack of private spaces to have discussions with team members in the ED impacted team collaboration negatively. Factors like central location of the physicians’ workstation with increased visibility to and from the different locations on the unit (Gharaveis et al, 2018), increased staff-to-staff visibility (Gharaveis et al, 2020), and proximity to the nurse stations are other factors that positively impact collaboration in the ED. A longitudinal case study conducted at three hospitals in Australia examined three different workstation layouts—an open staff workstation with no structural barriers or glass windows, a semi-open staff workstation with glass windows and an open doorway, and a fully enclosed workstation with glass windows in the door (Gum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Holtrop et al (2016) [29] introduce using MMR in the case of health services research to examine the potential for innovations in MMR procedures and to illustrate these points through a project on care management that used a convergent mixed methods design. Gharaveis et al (2019) [30] apply the mixed methods study to deliver empirical evidence on the influence of visibility on healthcare teamwork in Emergency Departments. Bakon & Millichamp (2017) [31] in the regional Australian hospital environment based on mixed methods, research the handover process and conclude that to deliver an optimal nursing handover from the emergency department to various wards, handovers should be structured and provide standardized content.…”
Section: -Theoretical Backgroundmentioning
confidence: 99%